Synchronized neural oscillations and the pathophysiology of Parkinson's disease. - Oswal, A; Brown, P; Litvak, V (2013)
PURPOSE OF THE REVIEW: Developments in functional neurosurgery for movement disorders and recent advances in electrophysiological techniques have allowed important insights into the role of oscillations in corticobasal ganglia circuits, both in health and in neurological disease states. Here we review recent developments in our understanding of how abnormally synchronized oscillatory activity within the corticobasal ganglia loop may play a key role in the pathophysiology of cognitive and motor phenotypes in Parkinson's disease. RECENT FINDINGS: Recent developments highlight the motor and non-motor roles of α, β and γ oscillations in the context of Parkinson's disease. They also emphasize the importance of oscillatory coupling between basal ganglia and cortex and draw attention to the importance of interactions between different frequency bands. SUMMARY: Oscillatory activities across multiple frequency bands and their cross-frequency interactions within spatially segregated loops of the basal ganglia-thalamo-cortical system may relate to distinct components of clinical impairment, both motor and non-motor. It is hoped that this characterization will lead to improved interventions like deep brain stimulation, tailored to specific components of clinical impairment and their associated spatial and spectral signatures.